Analysis of Islamic Religious Education Curriculum Based on Student Independence at Al-Hamidiyah Bawu Islamic Boarding School - Sarobila Taqikumul Harro; Muhammad Natsir (Universitas Islam Sultan Agung, 2026)
This study aims to analyse the concept and implementation of an independence-based Islamic Religious Education (IRE) curriculum in shaping the character of students at the Al-Hamidiyyah Bawu Islamic Boarding School. This study employs a qualitative approach using a case study design. Data collection techniques include interviews, observation, and documentation, with the researcher serving as the primary instrument. Data validity was tested through source triangulation, whilst data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that the independence-based Islamic Education curriculum is designed holistically by integrating academic aspects with character development. Independence is understood as the ability to manage oneself, take responsibility, and make decisions based on Islamic values. The curriculum is implemented through a combination of traditional and modern teaching methods, as well as the integration of classroom learning and dormitory life within a 24-hour boarding school system. The process of habit formation, the example set by teachers, and the entrusting of responsibilities to students serve as the primary strategies for the internalisation of the value of independence. Evaluation is conducted comprehensively, covering cognitive, affective, and psychomotor aspects, which demonstrate an improvement in students’ discipline, responsibility, and self-confidence. Nevertheless, the implementation of the curriculum faces challenges such as differences in the students’ backgrounds and the influence of technology. However, supporting factors such as the commitment of the teachers, a conducive boarding school environment, and a consistent disciplinary system are able to optimise the implementation of the curriculum. Thus, the independence-based PAI curriculum has proven effective in shaping students’ characters to be independent, disciplined, and responsible. This study recommends strengthening the aspects of life skills and entrepreneurship in the future development of the pesantren curriculum.